Activities of Daily Living, Depression, and Quality of Life in Parkinson’s Disease - Lawrence, B.; Gasson, Natalie; Kane, Robert; Bucks, R.; Loftus, Andrea (Public Library of Science, 2014)
This study examined whether activities of daily living (ADL) mediate the relationship between depression and health-related quality of life (HR-QOL) in people with Parkinson’s disease (PD). A cross-sectional, correlational research design examined data from 174 participants who completed the Geriatric Depression Scale (GDS-15), Parkinson’s Disease Questionnaire-39 (PDQ-39), and Unified Parkinson’s Disease Rating Scale-section 2 (UPDRS-section 2 [ADL]). Multiple Regression Analysis (MRA) was used to examine the mediator model. Depression and ADL significantly (p<.001) predicted HR-QOL, and depression significantly (p<.001) predicted ADL. Whilst ADL did not impact on the relationship between depression and HRQOL, there was a significant (p<.001) indirect effect of depression on HR-QOL via ADL, suggesting both direct and indirect (via ADL) effects of depression on HR-QOL. The magnitude of this effect was moderate (R2 = .13). People with PD who report depression also experience greater difficulty completing ADL, which impacts upon their HR-QOL. It is recommended that clinicians adopt a multidisciplinary approach to care by combining pharmacological treatments with psycho/occupational therapy, thereby alleviating the heterogeneous impact of motor and non-motor symptoms on HR-QOL in people with PD.